THE ARTISTIC FEATURES AND STYLISTIC EFFECTS OF TRANSLATION OF CHINESE AND KAZAKH PROVERBS - Dauletali , A.; Wen, Xu (Journal of Oriental Studies, 2024)
This study delves into the extensive body of research on proverbs in both Chinese and Kazakh languages. Scholars examining Chinese proverbs often approach the categorization and conceptual distinctions from three primary perspectives: 1) proverbs and sayings are grouped under the broader concept of "common sayings"; 2) within the concept of "proverbs," both terms are encompassed under "folk speech"; and 3) in translation, "proverbs" correspond to the Chinese term for proverbs, while "common sayings" align with the concept of proverbs as understood in Kazakh. Our research adopts the third perspective. Additionally, we explore the classification of Chinese expressions known as "歇后语" (Afterwords), which translates into Kazakh as "аллегориялық астарлы сөз" (metaphorical word). Unlike Chinese, where proverbs and proverbs are distinct, Kazakh language sources such as books, collections, and dictionaries often conflate the two, distinguishing proverbs with dashes and writing proverbs as a single unit without commas. Therefore, distinguishing between proverbs, sayings, and metaphors is crucial for accurate translation and understanding in both languages. Keywords: Chinese, Kazakh, proverbs, translation, artistic features, stylistic methods.